INVESTMENT IN HIGHER EDUCATION VERSUS ECONOMIC GROWTH – A PROPOSAL FOR THE DECOMPOSITION OF THE MRW MODEL FOR POLAND - Kowalska, Iwona; Banduła, Bartosz (Acta Scientiarum Polonorum. Oeconomia, 2017)
Higher education has become an increasingly knowledge-based sector of the present-day economy. The state faces the issues of financing higher education and assessing the effects of investment in the sector of higher education. The aim of this article is to determine the impact of investment expenditure on higher education (including the resources from the EU funds) on Poland’s economic growth as measured by the GDP growth rate. The research hypothesis of the article is that the economic growth that is caused by investment in higher education with the contribution of the EU funds results in a higher GDP growth than in the case when there is no access to such resources. The results of the research indicate that increased investment in higher education, which was the result of the availability of the EU structural funds, influenced the increase in human capital in Poland and raised its impact on the GDP growth rate.